Proposed pixel for custom laser doppler vibrometry camera - Jackson, Stephen (2012)
Non-destructive testing is an important field of research in many areas of industry and science. This field covers methods that test some property of an object while not impacting its future usefulness. This project is specifically interested in a method of NDE called Laser Doppler Vibrometry (LDV), which uses light to probe the motion of an object's surface.